Isolation of methicilin-resistant staphylococcus aureus (MRSA) from cats and dogs at University Veterinary Hospital, Universiti Putra Malaysia - Erkihun Aklilu; Zunita, Z. (2008)
Methicillin-resistant Staphylococcus aures (MRSA) is one of a major pathogen causing nosocomial infections. Pet animals especially cats and dogs have emerged as potential reservoirs for human infections. This study was conducted to know the occurrence of MRSA in pets (cats and dogs) admitted to the university small animal hospital. To this end nasal and perennial swabs were collected from 50 cats and 50 dogs. MRSA was isolated in 8% (8/100) of all the 100 pets sampled at the university small animal hospital. Out of the 50 dogs sampled 10 %( 5/50) were found to harbor MRSA and out of the 50 cats sampled 6 %( 3/50) were MRSA positive based on bacteriological examinations. The percentage of isolation from the current study is quite higher as compared to similar studies conducted earlier.